On the Lead Time of a Periodic Screening Program - Maier, Berthold J. (Methods of Information in Medicine, 1983)
Many parameters are needed in the assessment of the benefits of a periodic screening program. In this paper we present formulas for two of them: the proportion SP of patients detected and the lead time of such a program. The lead time is the time by which the disease is detected earlier due to screening. We also give a lower bound for the mean lead time L in terms of the mean sojourn time in a certain preclinical state P and of the sensitivity of the screening test in this state P only. Finally, we indicate how the mean sojourn time and, under certain assumptions, even the sensitivity are estimated from the results during the initial phase of the screening program.
Keywords: Screening; Lead Time; Sensitivity